Sin(9x)-cos(9x) *write the expression in terms of sine only

Use the formula of the sine of a sum or difference: sin(α – β) = sinα·cosβ – sinβ·cosα.

Note that √(2)/2 = sin(π/4) = cos(π/4).

Then sin 9x – cos 9x = √(2) (√(2)/2 ·sin 9x – √(2)/2· cos 9x) = √(2) (cos(π/4) ·sin 9x – sin(π/4)· cos 9x) =

√(2) sin(9x – π/4)

Thanks so much!

You are welcome.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up